2022
DOI: 10.1002/advs.202201339
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Double‐Heterojunctional Electrocatalyst for Hydrogen Evolution

Abstract: The active sites and charge/mass transfer properties in electrocatalysts play vital roles in kinetics and thermodynamics of electrocatalysis, and impose direct impacts on electrocatalytic performance, which cannot be achieved by a simplex structure. As a prototype, the authors propose a double-heterojunctional nanostructure of NiS 2 /Ni 3 C@C containing NiS 2 /Ni 3 C and Ni 3 C/C heterojunctions as a general model to optimize the above issues and boost electrocatalytic performance. During the thermal reorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 45 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…The results demonstrated that the highest performance was accomplished at an immersion Ni­(NO 3 ) 2 solution concentration of 0.75 mol·L –1 . The Nyquist plots of Ni­(PO 3 ) 2 -CoP 4 /CoMoO 4 /NF (∼0.42 Ω) exhibits the lowest charge-transferring resistance ( R ct ) at the overpotential of 20 mV than CoP 4 /CoMoO 4 /NF (∼1.70 Ω), Ni­(PO 3 ) 2 /NF (∼3.41 Ω), and CoMoO 4 /NF (∼4.93 Ω), respectively (Figure f), confirming high faradaic efficiency and rapid electron transfer …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results demonstrated that the highest performance was accomplished at an immersion Ni­(NO 3 ) 2 solution concentration of 0.75 mol·L –1 . The Nyquist plots of Ni­(PO 3 ) 2 -CoP 4 /CoMoO 4 /NF (∼0.42 Ω) exhibits the lowest charge-transferring resistance ( R ct ) at the overpotential of 20 mV than CoP 4 /CoMoO 4 /NF (∼1.70 Ω), Ni­(PO 3 ) 2 /NF (∼3.41 Ω), and CoMoO 4 /NF (∼4.93 Ω), respectively (Figure f), confirming high faradaic efficiency and rapid electron transfer …”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 4b 4f), confirming high faradaic efficiency and rapid electron transfer. 60 The normalized polarization curves by ECSA of Ni(PO 3 ) 2 -CoP 4 /CoMoO 4 /NF still exhibit higher intrinsic activities than that of CoP 4 /CoMoO 4 /NF, Ni(PO 3 ) 2 /NF, and CoMoO 4 /NF, proving again that the multi-interface nanostructure has excellent catalytic activity for HER (Figure S18). Additionally, the turnover frequency value (Figure S19) of the Ni(PO 3 ) 2 -CoP 4 /CoMoO 4 /NF catalyst is 1.039 s −1 at the overpotential of 50 mV, which is greater than 0.329, 0.355, and 0.058 s −1 for CoP 4 /CoMoO 4 /NF, Ni(PO 3 ) 2 /NF, and CoMoO 4 /NF, respectively, demonstrating the elevated number of active sites and significantly promoted the HER performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results fully demonstrate that the NiSe 2 nanoparticles sandwiched between the two layered structures can effectively optimize the overpotential of MoS 2 /rGO. Furthermore, multiple interfacial nanostructures can greatly improve the contribution of a single interface to performance, and this new multi-interfacial nanostructure constructed by the three composites acting together can facilitate the OER performance [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the Tafel slope of CS‐2 (201 mV dec −1 ) was smaller than SnO 2 (229 mV dec −1 ) and g‐C 3 N 4 (211 mV dec −1 ), revealing that the sluggish hydrogen evolution kinetics had been significantly accelerated after the heterojunction formed (Figure S14c , Supporting Information). [ 52 , 53 , 54 ] The photoelectrochemical performances of other composite samples were also compared to illustrate the effect of g‐C 3 N 4 content. The CS‐2 showed the highest current density among three composites.…”
Section: Resultsmentioning
confidence: 99%